PRODUKSI DAN PRODUKTIVITAS TUNA OLEH KAPAL TUNA LONGLINE YANG BERBASIS DI PPN PALABUHANRATU - Mohammad Imron; Roza Yusfiandayani; Mulyono S. Baskoro (Fakultas Perikanan dan Ilmu Kelautan, 2019)
Tuna fishing productivity can be seen from the production of landed production per attempt. The archipelago fishing port Palabuhanratu has become one of the active fishing ports in the southern coastal region in Java Island and it’s one of the centers of capture fisheries in the area of West Java Province. Tuna longline is an industrial-scale fishing unit to catch tuna as an export commodity. Tuna production in PPN Palabuhanratu experienced had a significant increase from 2010 to 2014. In 2014-2018 tuna production in PPN Palabuhanratu experienced had a quite drastic decline. In 2019, production will increase to 1,091,612 tons. Landing Per Unit Effort (LPUE) is used in fisheries research to indicate the abundance of resources used to conduct stock assessments when estimating the relative abundance of an exploited species. The composition of tuna catches by longline tuna vessels consists of yellowfin tuna (Thunnus albacores), big eye tuna (Thunnus obesus), and albakor tuna (Thunnus alalunga). Tuna production which was landed at PPN Palabuhanratu from 2010-2019 experienced is fluctuative. In 2010 the production of yellowfin tuna was 444,952 tons, big eye tuna was 979,189 tons, albakor tuna was 122,671 tons. In 2019 the production of yellowfin tuna was 617,992 tons, big eye tuna was 240,487 tons, albakor tuna was 233,133 tons. The highest productivity occurred in yellowfin tuna in 2014 with a LPUE value of 6,09 with a production of 2,448,171 tons with a total effort of 402. Productivity has fluctuated every year.